Características psicométricas da escala de impulsividade de Barratt em adolescentes - Vieira, Heloísa de Moura (2014)
Aiming to measure impulsivity to better forensic psychological assessment, considering that the construct is closely related to several psychiatric disorders and Antisocial personality disorders. The Barratt Impulsiveness Scale is one of the most suitable to perform the evaluation and there are still no patterning in Brazil. The research objective was to evaluate the psychometric characteristics of reliability and validity of the Barratt Impulsiveness Scale for teenagers, male, applied in one hundred seventy-seven subjects, between 14 and 20 years, in Curitiba and metropolitan region, Paraná. The participants were divided into three groups: Athletes; High school students; University. The internal consistency, measured by Cronbach's alpha was considered adequate, but the reliability, calculated using the Pearson correlation found was borderline. It was not possible to calculate the factor analysis, because it did not complete the necessary requisites. There was no evidence of criterion validity by comparing the results between the groups athletes, university and high school students. The test showed some important psychometric parameters suitable for male adolescents.